The impact of alcoholic extract of Fenugreek and Nigella stiva in high density proteins and Low density proteins in health rabbits and effected of liver functional disorder (Journal of Hama University, 2022)
The study was conducted on rabbits males at ages 6 months. The target of the study was to knowledge the impact each of alcohol extraction of fenugreek seeds and nigella stiva.seeds in the healthy rabbits high density proteins and Low density proteins in disordered functional in liver activity using 4th Carbon Chloride. The population study were divided into 10 groups, the first group was coded as G1 (included 6 rabbits), and considered as control group, It had been provided with water and food only, the second group was included 6 rabbits and coded as G2 that was taken alcohol extraction of fenugreek with dose 500 mg /kg while G3 group was included 6 rabbits and taken alcohol extraction of fenugreek with dose 1000 mg/kg. The fourth group was coded as G4 and involved 6 rabbits that were taken alcohol extraction of Nigella Stiva with dose 200 mg./kg. The fifth group was coded as G5 and involved 6 rabbits that were taken alcohol extraction of Nigella Stiva with dose 300 mg./kg. The sixth group was coded as G6 and involved 6 rabbits that were taken dose as 1 ml/kg of live weight of 4th Carbon Chloride weekly for 4 weeks. The seventh group was coded as G7 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of fenugreek with dose 500 mg /kg. The eighth group was coded as G8 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of fenugreek with dose 1000 mg /kg. The ninth group was coded as G9 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of Nigella Stiva with dose 200 mg./kg. The tenth group was coded as G10 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of Nigella  Stivawith dose 300 mg./kg. The results of the study showed that the treatment of rabbits, either with alcohol extraction of fenugreek seeds and nigella stiva.seeds, did not lead to a significant difference (P>0.05) between the values ​​of (LDL) among the rabbits of the negative control group compared with its values ​​in the groups of healthy experimental rabbits, while these results showed that the treatment of groups of experimental rabbits with liver dysfunction and treated with either alcohol extraction of fenugreek seeds and nigella stiva.seeds led to a significant decrease of P≤0.05 in the level of (LDL) compared to its level in the group of positive control rabbits, and this treatment also led to a significant increase of P ≤ 0.05 in the level of (HDL) in these groups of the experiment compared with the level of (HDL) in the rabbits of the positive control group.